ANALYSIS OF THE EFFECTIVENESS OF INSTRUMENTS AND IMPLEMENTATION OF SUMMATIVE EVALUATION IN TAHFIZH EDUCATION: CASE STUDY OF MTS AL-FATAH BOYOLALI - Efri Joni; Ari Anshori (Proceeding of International Conference of Islamic Education, 2025)
This research analyzes the quality of instruments and the effectiveness of summative evaluation implementation in tahfizh education at MTs Al-Fatah Boyolali. This research uses a qualitative research method with a descriptive approach. In collecting data, researchers used observation, interview, and documentation methods. The research results showed that the oral assessment rubric, which includes memorization fluency (40%), tajweed and makhraj (40%), and time accuracy (10%), is valid for measuring memorization, but does not include understanding the meaning of the verse due to the design of the tahfizh program which focuses on memorization. Time limitations, especially in the randomized test (mubādarah) which covers 70% of the evaluation, affect the accuracy of the assessment. The implementation of summative evaluation is effective in measuring students discipline, supported by graduation motivation, with an average score of 75 (odd semester) and 80 (even semester) for 75 students. The distribution of even semester grades showed 20 students scored A (91-100), 30 students scored B (81-90), 20 students scored C (71-80), and 5 students scored D (<70), with 27 passing and 3 not passing out of 30 students. Implementation constraints include student anxiety, stress-induced thrush, and teacher or student absenteeism. This research recommends the addition of meaning comprehension assessment, better time management, and psychological support to improve the effectiveness of tahfizh evaluation.